2020
DOI: 10.3892/or.2020.7617
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid induces cell cycle arrest and apoptosis via the TGF‑β1/Smad3 signaling pathway in human colon cancer HCT‑116 cells

Abstract: Colorectal carcinoma (CRC) is a major type of malignancy worldwide. Ellagic acid (EA), a natural phenolic constituent, has been shown to exhibit anticancer effects. In our previous study, it was shown that EA inhibited proliferation of CRC cells. Additionally, microarray analysis revealed 4,738 differentially expressed genes (DEGs) which were associated with multiple cellular events, including cell growth, apoptosis and angiogenesis. However, the associated pathways had not been validated. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In the present study, it was identified to be hypermethylated in gene body but was related with up-regulated gene expression. Of the 6 drugs targeting CA9, benzthiazide [ 43 ], hydroflumethiazide [ 44 ], WX-G250 [ 45 ], and ellagic acid [ 46 ] have shown antitumor properties. SLC7A11 encodes the light chain subunit of cystine/glutamate antiporter system xc—and is involved in glutamine metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, it was identified to be hypermethylated in gene body but was related with up-regulated gene expression. Of the 6 drugs targeting CA9, benzthiazide [ 43 ], hydroflumethiazide [ 44 ], WX-G250 [ 45 ], and ellagic acid [ 46 ] have shown antitumor properties. SLC7A11 encodes the light chain subunit of cystine/glutamate antiporter system xc—and is involved in glutamine metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, immunofluorescence costaining verified that α-SMA-positive cells undergo ferroptotic processes. A study revealed that EA can inhibit colon cancer and esophageal cancer development by inducing cell cycle arrest and apoptosis [ 41 , 42 ]. In our studies, the ferroptosis inhibitor ferrostatin-1 relieved the growth inhibition of HSCs induced by EA, while ZVAD-FMK (an apoptosis inhibitor) could not.…”
Section: Discussionmentioning
confidence: 99%
“…Ellagic acid (EA), a natural phenolic constituent, has been shown to exhibit anti-cancer effects. Zhao studied EA targeted to the TGFbeta1/Smad3 pathway on HCT116 cells, which might be potentially used to treat CRC [27]. Additionally, they also found that EA modified a large number of cellular functions, including proliferation, apoptosis, cell cycle, and angiogenesis [28].…”
Section: Discussionmentioning
confidence: 99%